Comparative analysis of anatomic parameters of the eyeball in children with ametropia, congenital glaucoma, aphakia and artiphakia - L. S. Khamraeva; L. Yu. Bobokha; Ch. K. Abdurakhmanova; Z. A. Makhmudova (Российский офтальмологический журнал, 2019)
Purpose. To conduct a comparative analysis of the anatomical parameters of the eyeball in children with ametropia, congenital glaucoma, aphakia and artiphakia.Material and methods. The study involved 73 patients (146 eyes) aged 5 to 12 years with ametropia, congenital glaucoma, aphakia and artiphakia and was carried out on an ultrasonic device STRONG 6000 T in the A-scan mode with the 10 MHz sensor set for three points.Results. A significant increase in the size of axial length of the eyeball in moderate and high myopia and in the vertical size in high myopia were revealed. In high hyperopia, sagittal dimensions were reduced while the transverse dimensions were a bit greater than the sagittal ones. In far-advanced stage of congenital glaucoma, a significant increase in eyeball dimensions was noted both in the axial direction and in the transverse — horizontal direction. No significant differences in sagittal and transverse dimensions were noted in aphakia and artiphakia. Conclusion. For a comprehensive assessment of the clinical course of the disease, in particular as concerns the condition of the fibrous capsule of the eye in children with ametropia, congenital glaucoma, aphakia and artiphakia, echobiometric indicators characterizing sagittal and transverse (vertical and horizontal) sizes of the eyeball should be taken into account.